Emerging Trends in Factors Associated with Behavioral Difficulties in Boys and Girls - Mora Alvarado , Karla Gabriela; Almeida Monge , Elka Jennifer; Álvarez Cadena, Kerly Angela; Pilamunga Asacata, Diana Elizabeth (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
To carry out a bibliographic review of the factors associated with behavioral difficulties in children, but there are global data on these variables. Purpose: The purpose of this study was to review the literature on the factors associated with behavioral difficulties in boys and girls to identify the most influential countries, authors, magazines and institutions, their structures and research directions. Design: This review is based on bibliometric and network analysis of literature published in Scopus and Web of Science. A total of 110 scientifically mapped articles were found in this area.